The Role of Master Teacher Babussalam (Syekh Hasyim Al-Syarwani) and the Khalifah in Overcoming Public Problems - Riono Hardiman; Lahmuddin Lahmuddin; Abdurrahman Abdurrahman (Budapest International Research and Critics University, 2021)
This study aims to find out The Role of Master Teacher Babussalam (Syekh Hasyim Al-Syarwani) and the Khalifah in Overcoming Public Problems. The type of research used in this research is field study research (qualitative descriptive). Researchers will qualitatively review and describe the results of the reality interviews found in the field, namely by interviewing Tuan Guru / Syekh Babussalam, the caliphs, congregations, and the community around the Sufi institution Tareqat Naqsyabandiyah Babussalam, related to various problems of the ummah and their alleviation. The roles of Tuan Guru Babussalam (Syekh Hasyim Syarwani) and the caliphs are as Islamic counselors, Al- Quran teachers (educators), healers, priests or leaders, caregivers and guides. As an Islamic Counselor, the main task of the master teacher and the caliph is to develop the teachings of the Naqsyabandiyah Order. However, because many people expect assistance and advice on solutions to various life problems. So that master teachers and caliphs help with advice, approaches and wisdom so that people enter the following dimensions. (1) The spiritual dimension, by directing the people to ask forgiveness from Allah SWT, as well as practicing the practices of the Shari'a such as guarding congregational prayers, praying tahajjud to serve parents, giving alms while asking Allah SWT for help. It is different if the problems of life are experienced by the congregation of the Naqsyabandiyah Order, the teacher and the caliphs recommend that they talk and practice the dhikr that is taught. As a healer, it can be seen in the service to the people who come. With the aim of asking for help in healing various diseases, namely to ask for recovery from psychological, medical and non-medical illnesses. With given traditional medicinal ingredients, as well as help with water therapy that has been prayed for by the teacher or the caliph.